Non‐performing assets and its determinants in the Indian banking system: An empirical analysis using dynamic panel data models. (18th August 2020) - Mishra, Aswini Kumar; Jain, Shikhar; Abid, Mohammad
Abstract: Non‐performing assets (NPAs) in the Indian banking system are currently one of the biggest financial threats to the Indian economy. The gross NPAs for Indian banks have increased by nearly four times from nearly USD 35 billion as of March 2014 to more than USD 150 billion as of March 2018. The factors responsible for this are political, macroeconomic as well as bank‐specific in nature. In this study, we study the determinants of NPAs for Indian banks by using a panel dataset for 40 public and private banks in India, for the period March 2010 to June 2019 (quarterly‐frequency). Among the macro‐economic variables, we find the Index of Industrial Production (IIP), Consumer Price Index (CPI) Inflation, policy repo rate, and exchange rate to be significant determinants of NPAs. Among the bank‐specific variables, we find gross loans and advances, provisions and contingencies, income on investments, and sector of bank (Public vs. Private) to be significant determinants of NPAs. We also find the role of demonetization (2016) towards influencing the NPAs of Indian banks, to be insignificant. Finally, we also provide some policy implications and remedial measures to tackle the problem of NPAs.